Exenatide ameliorates hepatic steatosis and attenuates fat mass and FTO gene expression through PI3K signaling pathway in nonalcoholic fatty liver disease - Li,Shan (2018)
Non-alcoholic fatty liver disease (NAFLD) is a common disease associated with metabolic syndrome and can lead to life-threatening complications like hepatic carcinoma and cirrhosis. Exenatide, a glucagon-like peptide-1 (GLP-1) receptor agonist antidiabetic drug, has the capacity to overcome insulin resistance and attenuate hepatic steatosis but the specific underlying mechanism is unclear. This study was designed to investigate the underlying molecular mechanisms of exenatide therapy on NAFLD. We used in vivo and in vitro techniques to investigate the protective effects of exenatide on fatty liver via fat mass and obesity associated gene (FTO) in a high-fat (HF) diet-induced NAFLD animal model and related cell culture model. Exenatide significantly decreased body weight, serum glucose, insulin, insulin resistance, serum free fatty acid, triglyceride, total cholesterol, low-density lipoprotein, aspartate aminotransferase, and alanine aminotransferase levels in HF-induced obese rabbits. Histological analysis showed that exenatide significantly reversed HF-induced lipid accumulation and inflammatory changes accompanied by decreased FTO mRNA and protein expression, which were abrogated by PI3K inhibitor LY294002. This study indicated that pharmacological interventions with GLP-1 may represent a promising therapeutic strategy for NAFLD.